SOME CHARACTERISTICS OF THE EARTHQUAKE CATALOG AND THE SEISMIC PROCESS ACCORDING TO THE KNET NETWORK - N. A. Sycheva (Геодинамика и тектонофизика)
Some characteristics of the earthquake catalog and seismic process are considered. The catalog is obtained according to the KNET network (KN-code in FSDN, International Federation of Digital Seismograph Networks, that is operated by Research Station of RAS, RS RAS) and contains more than 10000 earthquake parameters from 1994 to 2020. The catalog and seismicity characteristics were determined the whole catalog as well as the catalog that is limited by the coordinates of the Bishkek geodynamic polygon (BGP). Statistical analysis of arrival times of direct P- and S-waves registered at KNET network stations was carried out. The maximum P- and S-waves were registered at AAK station, the minimum – at ULHL station. The territory of the BGP is covered by great P-traces density. We analyzed earthquake localization errors, i.e. the difference between the observed and calculated arrival times of P-and S-wave fronts (RMS), horizontal error (ERH, epicenter) and vertical error (ERZ, depth). Occurred on the BGP territory earthquakes have minimum values of the considered errors. The representative sample is defined: for the whole catalog it includes K≥7.2 earthquakes and for the limited by BGP coordinates catalog – K≥6.7. Statistical characteristics of the representative part of the catalog in terms of time and depth are determined. The temporal distribution of earthquakes by energy classes is constructed and the absence of positive or negative trends in the number of events is noted. Spatial distribution of earthquakes by depth – 0–5, 5–10, 10–15 and more than 15 km is constructed. The smallest errors of earthquake depth determination have the events that occurred on the BGP territory. During the study 46 moderate earthquakes with K≥12 occurred. The most part of these events happened in the North Tien Shan seismgenic zone. 22 events were determined with K≥10 followed by aftershock sequences and give some aftershock characteristics. The most events with aftershocks occurred in the eastern part of the Kyrgyz ridge. The distribution of earthquake numbers and STD intensity is constructed. Zones of seismic activity and maximum intense Earth’s crust deformation are identified. The Gutenberg – Richter law and provisions of nonextensive statistical physics were used to describe the energy distribution function of earthquakes.